The Effect Of Ethanol Extract Of Garden Balsamâs Leaves (Impatiens balsamina) To Mortality Of Anopheles aconitus Larvae - Rizki, Mutiani; Handayani, Sutartinah Sri; Nugroho, Dian (Nexus Kedokteran Translasional, 2016)
Introduction: The prevalence of malaria in Indonesia is still high. One of the vector which transmitted malaria in Indonesia is Anopheles aconitus. During this time, abate (temephos) was being used to eliminate the mosquito larvae. The long-term use of abate (temephos) is not good for environment and perhaps may cause resistance on mosquito. Garden Balsamâs leaves (Impatiens balsamina) contain substances which can be larvacide, so the researcher want to prove whether the ethanol extract of Garden Balsamâs leaves (Impatiens balsamina) have effect to mortality of Anopheles aconitus. Methods: This research used laboratory experimental method with the post test only control group design. The object of this research was Anopheles aconitus larvae which divided into 7 groups, each group contain 25 larvae and this research was replicated 4 times. For the negative control, 100 ml aquadest was used. And for the other 6 groups, contain 300 mg, 500 mg, 700 mg, 900 mg, 1100 mg, 1300 mg extract in 100 ml aquadest. The data was analyzed by Linear Regression and Probit test. Results : Linear Regression test show that the percentage of extract effect to larvae mortality is 88,3% and the rest 11.7%Â  was effected by the other variable. The linear equation is Yâ= 3.116 + 0,02X . Probit test show LC50 is 405.580 mg/100 ml and LC99 is 1352.177 mg/100 ml. Conclusion: There is effect of ethanol extract of Garden Balsamâs leaves (Impatiens balsamina) to the mortality of Anopheles aconitus larvae. The LC50 is 405.580 mg/100 ml and LC99 is 1352.177 mg/100 ml. Keywords: extract of Garden Balsamâs leaves, mortality, Anopheles aconitus larvae